Serogical survey for neutralising antibodies to SVD - ΠΑΠΠΟΥΣ, Χ.; ΔΗΜΗΤΡΙΑΔΗΣ, Ι.; ΠΑΝΝΑΚΙΔΗΣ, Δ.; ΓΚΩΓΚΟΣ, Α.; ΖΑΦΕΙΡΙΟΥ, Γ.; ΖΟΥΠΙΔΗΣ, Α.; ΘΕΟΔΩΡΟΥ, Ε.; ΙΑΚΩΒΙΔΗΣ, Γ.; ΛΥΡΙΤΣΗΣ, Β.; ΜΟΣΧΟΒΙΤΗΣ, Σ.; ΤΣΙΛΙΟΥ, Χ.; ΤΣΙΡΩΝΗΣ, Λ. (Journal of the Hellenic Veterinary Medical Society, 2019)
A serological survey for neutralising antibodies to SVD was carried out mainly in slaughtered pigs from the area where SVD virus was isolated (Aspropyrgos-Attikis) in July 1979 as well as from other areas in 9 départements. 214 Sera of 18 herds from the outbreak area and its vicinity were tested. 4 herds of the outbreal area were positive. The percentage of positive sera was 96-100%. 94% of them had a titre- >=1:128 the results were confirmed by double immunodiffusion assay. 412 sera of 45 herd from 9 Departements were negativ.